Knowledge, sources of information, and risk factors for sexually transmitted infections among secondary school youth in Zaria, Northern Nigeria - Aliyu, Alhaji A.; Dahiru, Tukur; Ladan, Awwal M.; Shehu, Adamu U.; Abubakar, Aisha A.; Oyefabi, Adegboyega M.; Yahaya, Shamsudeen S. (Medknow Publications, 2013)
Background: Sexually transmitted infections (STIs) are responsible for a variety of health problems especially among the youth who engage in risky sexual behavior. There are few studies that describe STIs among the youths in Northern Nigeria. The objective of the study was to assess knowledge of STIs and risk factors among secondary school youth. Materials and Methods: This was a cross‑sectional study in which structured, self‑administered questionnaire was used to collect data on socio‑demographics, knowledge on STIs, and risk factors. Three senior secondary schools were purposively selected for the study. Results: A total of 1765 youths aged 10‑30 years with mean age of 16.9 ± 2.0 years participated in the study. 1371 (77.7%) and 394 (22.3%) were respectively Muslim and Christian. Mean age at first sexual intercourse was 16.7 ± 2.0 years.A majority (67.6%) of them heard about STIs; sources of information of STIs were school lessons 23.6%, mass media 23.3%, and health magazines 19.2%, respectively. Generally, knowledge on STIs was good as 75.4% of respondents knew how the disease is transmitted. This knowledge was significantly associated with class of student, place of treatment, and religious teaching (χ2 = 9.6, P = 0.047, χ2 = 22.1, P = 0.035 and 42.6, P = 0.001, respectively). Mean knowledge score was 0.698 ± 0.01. A majority of respondents were engaged in risky sexual behavior as only 16.2% use condom as a preventive measure. Eleven percent reported ever having an STI in the past and majority (52.8%) go to government hospital for treatment of acquired STI. 56% of the youth had two or more boy/girl friends and 30% had sexual relationships. Conclusion: It was concluded that secondary school youth had good knowledge about STIs; however, the opposite is true when it comes to preventive practice (use of condom). Interventions such as periodic publicity awareness and school seminars focusing on STI preventions are needed to control the disease among the youth.